2016
DOI: 10.1002/2015wr018444
|View full text |Cite
|
Sign up to set email alerts
|

Can a paleodrought record be used to reconstruct streamflow?: A case study for the Missouri River Basin

Abstract: Recent advances in paleoclimatology have revealed dramatic long‐term hydroclimatic variations that provide a context for limited historical records. A notable data set derived from a relatively dense network of paleoclimate proxy records in North America is the Living Blended Drought Atlas (LBDA): a gridded tree‐ring‐based reconstruction of summer Palmer Drought Severity Index. This index has been used to assess North American drought frequency, persistence, and spatial extent over the past two millennia. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 82 publications
(84 reference statements)
2
32
0
Order By: Relevance
“…have previously been used to assess the performance of streamflow models (Chen, Hao, Devineni, & Lall, 2014;Devineni, Lall, Pederson, & Cook, 2013;Ho et al, 2016). The comparison between streamflow before and after dam operation provides an approach to assessing the impact of the dam on either exacerbating or mitigating extreme events.…”
Section: Model Performance Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…have previously been used to assess the performance of streamflow models (Chen, Hao, Devineni, & Lall, 2014;Devineni, Lall, Pederson, & Cook, 2013;Ho et al, 2016). The comparison between streamflow before and after dam operation provides an approach to assessing the impact of the dam on either exacerbating or mitigating extreme events.…”
Section: Model Performance Metricsmentioning
confidence: 99%
“…A positive value indicates that the model has better predictive skill than using the climatology of the verification period.The RE and CE statistics are similar to the Nash-Sutcliffe efficiency score(McCuen, Knight, & Cutter, 2006;Nash & Sutcliffe, 1970) andhave previously been used to assess the performance of streamflow models(Chen, Hao, Devineni, & Lall, 2014;Devineni, Lall, Pederson, & Cook, 2013;Ho et al, 2016). Theoretically, the values of both RE and CE range from the negative infinity to a maximum of 1, with higher values indicating better prediction skill.…”
mentioning
confidence: 96%
“…We conclude that the BSM model improves upon the PCR model in cross validation with the CE statistic. Cook et al (), Devineni et al (), Ho et al () and Rao et al () all found results that were similar in their reconstructions; in particular, it was a bit more difficult to achieve positive values with the CE statistic than with the RE statistic, and hence a slightly greater number of negative values were encountered in the validation with this statistic.…”
Section: Resultsmentioning
confidence: 77%
“…Barnett et al (2010) were able to explain 44% to 65% variance in their streamflow reconstructions for the Upper Green River Basin. Ho et al (2016) were able to explain an even greater share of the variance in the Missouri River Basin, where the adjusted R 2 values of their reconstructions ranged from 0.56 to 0.90. However, there is a significant overlap in the range of R 2 values in this study with those in our study.…”
Section: Reconstruction Resultsmentioning
confidence: 99%
See 1 more Smart Citation